2020
DOI: 10.3389/fpsyt.2019.00993
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues in Online Psychotherapy: A Narrative Review

Abstract: Background: The provision of psychotherapy over distance using technology is a growing market reaching many patients and therefore the risks and benefits need to be known by all psychotherapists whether they themselves practice online or not. This comprehensive review of the main ethical arguments for and against different forms of online psychotherapy aims to enhance discussion of ethical issues in this growing area. Methods: A search of three databases (PubMed, PsycINFO, Web of Science) was conducted in Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
219
3
39

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(265 citation statements)
references
References 214 publications
4
219
3
39
Order By: Relevance
“…One of the future goals of public and private psychological organizations should be the promotion of specific training for psychologists and psychotherapists, with the following aims: (1) developing the basic skills in managing the effects of a pandemic and of emergency situations; and (2) sensitizing patients to online therapeutic relationship, providing the main rules and benefits of the process ( Stoll et al, 2020 ; Joint Task Force for the Development of Telepsychology Guidelines for Psychologists, 2013 ). On this line, a significant example is the Virginia Commonwealth University (VCU) which proposed PhDs in telepsychology, with the aim of training future psychologists in managing the psychological effects of the pandemic through an online psychology service ( Baylor et al, 2019 ).…”
Section: Telepsychology: Training and Promotion Of Psychological Wellmentioning
confidence: 99%
“…One of the future goals of public and private psychological organizations should be the promotion of specific training for psychologists and psychotherapists, with the following aims: (1) developing the basic skills in managing the effects of a pandemic and of emergency situations; and (2) sensitizing patients to online therapeutic relationship, providing the main rules and benefits of the process ( Stoll et al, 2020 ; Joint Task Force for the Development of Telepsychology Guidelines for Psychologists, 2013 ). On this line, a significant example is the Virginia Commonwealth University (VCU) which proposed PhDs in telepsychology, with the aim of training future psychologists in managing the psychological effects of the pandemic through an online psychology service ( Baylor et al, 2019 ).…”
Section: Telepsychology: Training and Promotion Of Psychological Wellmentioning
confidence: 99%
“…Survey studies have reported that approximately half of all respondent psychotherapists perceive telepsychotherapy as less effective than face-to-face psychotherapy (Gordon et al, 2015(Gordon et al, , 2016Schulze et al, 2018). Indeed, there are ethical arguments against the seamless implementation of online therapy, including (1) privacy, confidentiality, and security issues, (2) therapist competence and need for special training, (3) communication issues specific to technology, (4) research gaps, and (5) emergency issues (Stoll et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…DHI provide unique benefits, as proven during the SARS-CoV2-19 lock-down, but also bring potential pitfalls. Table 2 gives an overview on aspects regarding accessibility, the implementation of interventions itself, the evidence regarding interventions as well as economic aspects [ 4 ].…”
Section: Evidence-based Dhimentioning
confidence: 99%